2018
DOI: 10.1063/1.5048099
|View full text |Cite
|
Sign up to set email alerts
|

Direct observation of electron capture and emission processes by the time domain charge pumping measurement of MoS2 FET

Abstract: Understanding interface properties in MoS2 field effect transistors with a high-k gate insulator is critical for improving the performance of the device. Here, by applying the time domain charge pumping method, the elementary process for capture and emission of electrons to the interface states is monitored directly using a fast acquisition system. The main outcome is the detection of the clear difference in the capture and emission process of electrons to the interface states. In addition to the transient cur… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…Here, the recent demonstration of a natural thin‐body MoS 2 FET with an effective channel length of ≈ 3.9 nm has facilitated research on 2D layered channels due to overcoming the scaling limit of ≈ 5 nm for Si gate length . Although the dangling‐bond‐free surface of the layered channel is expected to ideally provide an electrically inert interface, there are many reports on the wide range of interface state densities ( D it ) from 10 11 to 10 13 eV −1 cm −2 for high‐ k top‐gate n ‐MoS 2 FET in reality, which must be reduced to improve the device performance. To date, several physical origins for D it have been proposed, which are summarized in Figure a.…”
Section: Introductionmentioning
confidence: 99%
“…Here, the recent demonstration of a natural thin‐body MoS 2 FET with an effective channel length of ≈ 3.9 nm has facilitated research on 2D layered channels due to overcoming the scaling limit of ≈ 5 nm for Si gate length . Although the dangling‐bond‐free surface of the layered channel is expected to ideally provide an electrically inert interface, there are many reports on the wide range of interface state densities ( D it ) from 10 11 to 10 13 eV −1 cm −2 for high‐ k top‐gate n ‐MoS 2 FET in reality, which must be reduced to improve the device performance. To date, several physical origins for D it have been proposed, which are summarized in Figure a.…”
Section: Introductionmentioning
confidence: 99%
“…Literature encompasses examples of materials like Ti/Au [156,157], Cr/Au [158,159], Ag/Au [160,161] and Ni/Au [162,163], Al [164,165] for realizing electrical contacts in MoS 2 FETs. It may be noted that MoS 2 FETs with Ag/Au contacts provides 60 times higher ON current (I ON ) compared to devices with Ti/Au contacts [166].…”
Section: Contact Materials Selection and Work Functionmentioning
confidence: 99%
“…However, detailed studies of the 2D heterostructure interface properties have been quite limited [6][7][8][9][10][11][12][13][14] because it is difficult to apply conventional C-V measurements to 2D systems. Therefore, we have faced this issue squarely in our work to date [15][16][17][18][19][20][21]. In this review article, the SiO 2 /Si interface properties revealed by many dedicated researchers are first compared with the fundamental properties of graphene and MoS 2 on the substrates.…”
Section: Introductionmentioning
confidence: 99%